Whole-brain magnetic resonance imaging of plaque burden and lenticulostriate arteries in patients with different types of stroke. (February 2019) - Wu, Fang; Zhang, Qian; Dong, Kai; Duan, Jiangang; Yang, Xiaoxu; Wu, Ye; Zhang, Ling; Li, Debiao; Fan, Zhaoyang; Yang, Qi
Background: Large-vessel atherosclerotic disease is an important pathogenesis of deep-perforator infarction (DPI). However, altered vessel walls of intracranial large arteries and distribution of small arteries in DPI are unclear because of the limited resolution of current imaging techniques. In this study the intracranial plaque burden and lenticulostriate artery (LSA) distribution in patients with recent DPI and non-DPI using whole-brain vessel-wall imaging (WB-VWI) were investigated. Methods: A total of 44 patients with recent DPI (23 patients) or non-DPI (21 patients) due to intracranial atherosclerotic disease were prospectively enrolled. WB-VWI was performed in all the patients using a three-dimensional T1-weighted vessel-wall magnetic resonance technique. Hemispheres with DPI and non-DPI were considered as the DPI group and non-DPI group, respectively. Hemispheres without a history of stroke were the control group. The intracranial plaque burden was compared between the DPI and non-DPI groups. The number and length of visualized LSA branches among DPI, non-DPI, and control groups were also evaluated. Results: A total of 77 hemispheres were analyzed (23 in the DPI group, 21 in the non-DPI group, and 33 in the control group). Plaque burden was lower ( p = 0.047) in the DPI group (82.0 ± 45.9 mm 3 ) compared with the non-DPI group (130.9 ± 90.3 mm 3 ). There was a significant reduction ( p = 0.002) in length of visualized LSA branches in the DPI group (74.1 ± 21.7 mm) compared with the control group (104.6 ± 33.3 mm). Conclusions: WB-VWI enables the combination of vessel-wall and LSA imaging in one image setting, which can provide information about plaque burden and LSA distribution.